2016
DOI: 10.1016/j.bbadis.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Novel effects of sphingosylphosphorylcholine on invasion of breast cancer: Involvement of matrix metalloproteinase-3 secretion leading to WNT activation

Abstract: Sphingosylphosphorylcholine (SPC) participates in several cellular processes including metastasis. SPC induces keratin reorganization and regulates the viscoelasticity of metastatic cancer cells including PANC-1 cancer cells leading to enhanced migration and invasion. The role of SPC and the relevant mechanism in invasion of breast cell are as yet unknown. SPC dose-dependently induces invasion of breast cancer cells or breast immortalized cells. Reverse transcription polymerase chain reaction and Western blot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Well known examples are the sphingosylphosphorylcholine (lysosphingomyelin), galactosylsphingosine (psychosine) and glucosylsphingosine, which consist on a SO LCB linked to phosphorylcholine, galactose and glucose, respectively. Different studies suggest that these LCB derivatives have important roles in cell function [48][49][50][51][52] and might contribute to different pathologies, including cancer [53,54] and lysosomal storage diseases [55][56][57][58].…”
Section: Sphingolipid Metabolism -An Overviewmentioning
confidence: 99%
“…Well known examples are the sphingosylphosphorylcholine (lysosphingomyelin), galactosylsphingosine (psychosine) and glucosylsphingosine, which consist on a SO LCB linked to phosphorylcholine, galactose and glucose, respectively. Different studies suggest that these LCB derivatives have important roles in cell function [48][49][50][51][52] and might contribute to different pathologies, including cancer [53,54] and lysosomal storage diseases [55][56][57][58].…”
Section: Sphingolipid Metabolism -An Overviewmentioning
confidence: 99%
“…MMP3 and DKK3 have been shown to have opposite effects on Wnt activation. MMP3 secretion has been shown to lead to increased Wnt activation [ 110 , 111 ], while increased DKK3 expression results in reduced Wnt activation [ 99 , 105 , 106 , 107 ]. The results presented in the current study thus appear to contradict these earlier findings, with both MMP3 and DKK3 expressed more highly in tumor compared to non-tumor tissue.…”
Section: Discussionmentioning
confidence: 99%
“…SPC induces invasion of MCF10A cells via secretion of MMP-3 and phosphorylation and reorganization of keratin 8. Sustained keratin phosphorylation leads to keratin loss ( Beil et al ., 2003 ; Kim et al ., 2015 , 2016 ). These results suggested that SPC might be involved in EMT.…”
Section: Resultsmentioning
confidence: 99%
“…Increased levels of SPC are found in atopic dermatitis, Niemann-Pick disease (NPD), and malignant ascites among patients with tumors ( Xiao et al ., 2001 ; Kurokawa et al ., 2009 ). SPC induces invasion via secretion of matrix metalloproteinase-3 (MMP-3) and perinuclear reorganization of keratin 8 (K8) filaments that contribute to the viscoelasticity of metastatic cancer cells ( Beil et al ., 2003 ; Kim et al ., 2015 , 2016 ).…”
Section: Introductionmentioning
confidence: 99%